D‐dimer to guide the intensity of anticoagulation in Chinese patients after mechanical heart valve replacement: a randomized controlled trial. (20th September 2017) - Zhang, L.; Zheng, X.; Long, Y.; Wu, M.; Chen, Y.; Yang, J.; Liu, Z.; Zhang, Z.
Abstract : Essentials Low anticoagulation intensity reduces bleeding but increases thrombosis during warfarin therapy. Elevated D‐dimer level is associated with increased thrombosis events. D‐dimer can be used to find potential thrombosis in those receiving low intensity therapy. D‐dimer‐guided therapy may be the optimal strategy for those with mechanical heart valve replacement. Summary: Background: Controversies remain regarding the optimal anticoagulation intensity for Chinese patients after mechanical heart valve replacement despite guidelines having recommended a standard anticoagulation intensity. Objectives: To investigate whether D‐dimer could be used to determine the optimal anticoagulation intensity in Chinese patients after mechanical heart valve replacement. Patients/Methods: This was a prospective, randomized controlled clinical study. A total of 748 patients following mechanical heart valve replacement in Wuhan Asia Heart Hospital were randomized to three groups at a ratio of 1 : 1 : 1. Patients in two control groups received warfarin therapy based on constant standard intensity (international normalized ratio [INR], 2.5–3.5; n  = 250) and low intensity (INR, 1.8–2.6; n  = 248), respectively. In the experimental group ( n  = 250), warfarin therapy was initiated at low intensity, then those with elevated D‐dimer levels were adjusted to standard intensity. All patients were followed‐up for 24 months until the occurrence of endpoints, including bleeding events, thrombotic events and all‐cause mortality. Results: A total of 718 patients were included in the analysis. Fifty‐three events occurred during follow‐up. There was less hemorrhage (3/240 vs. 16/241; hazard ratio [HR], 0.18; 95% confidence interval [CI], 0.07–0.45) and all‐cause mortality (4/240 vs. 12/241; HR, 0.33; 95% CI, 0.12–0.87) observed in the D‐dimer‐guided group than in the standard‐intensity group. A lower incidence of thrombotic events was also observed in the D‐dimer‐guided group when compared with the low‐intensity group (5/240 vs. 14/237; HR, 0.35; 95% CI, 0.14–0.85). Overall, the total events were less in the D‐dimer‐guided group (9/240) when compared with the other two control groups (24/241, 20/237; HR, 0.37, 0.44; 95% CI, 0.19–0.72, 0.21–0.90 Conclusions: The D‐dimer‐guided adjustment of anticoagulation intensity could reduce adverse events in Chinese patients after mechanical heart valve replacement. Trial Registry: NCT01996657; ClinicalTrials.gov.